Disposition effect pada Glamour Stocks Aplikasi Metode Vector Autoregression - Sutanto, Ervina; Arfianto, Erman Denny (Diponegoro Journal of Management, 2015)
This study aimed to see whether there is disposition effect in glamor stocks in the Indonesian market or not , in the period 2010 - 2012. Disposition effect is deviant behavior of investors to hold losses too long and realize profits too fast . Approaches to see the disposition effect is to look at the relationship between the variables of trading volume, volatility and returns.This study used a method Vector autoregression( VAR ). The data used in this study are the data of trading volume, volatility and weekly stock returns. The sample used was 10 glamor stocks the period January 2010 - December 2012. The VAR analysis using four methods to answer the research questions, namely the analysis of the VAR, Impulse Response Function ( IRF ), Variance Decomposition and Granger Causality Test.From the test results using the VAR analysis, showed that there was no disposition effect in glamor stocks on the Indonesia Stock Exchange. Based testing can be concluded that investors behave rationally in making investment decisions. The conclusions are based on test results that have been done. Results of Impulse Response Function ( IRF ) shows the response of a variable to another variable shock. Variance Decomposition results showed a variable response to the movement of his past variables. Furthermore causality test results indicate that there is no pattern of causality between variables.